2006
DOI: 10.1111/j.1460-9568.2006.05117.x
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus lesions increase impulsive action and decrease impulsive choice − mediation by enhanced incentive motivation?

Abstract: The subthalamic nucleus (STN) is traditionally thought of as part of a system involved in motor control but recent evidence suggests that it may also play a role in other psychological processes. Here we examined the effects of STN lesions on two measures of impulsivity and found that STN lesions increased 'impulsive action' (produced behavioral disinhibition), as measured by performance on a differential reinforcement of low rates of responding task, but decreased 'impulsive choice' (impulsive decision making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
109
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 67 publications
7
109
5
Order By: Relevance
“…These results were somewhat surprising given previous reports that suggested AMPH, at the doses tested here, decreases impulsivity (Barbelivien et al, 2008;Cardinal et al, 2000;deWit et al, 2002;Winstanley et al, 2003;van Gaalen et al, 2006). However, AMPH's effects on delay-discounting behavior are not unequivocal; it has been shown to increase (Evenden and Ryan, 1996;Cardinal et al, 2000) or have little to no effect on impulsive choice (Barbelivien et al, 2008;Uslaner and Robinson, 2006). One factor that has been suggested as a potential contributor to these inconsistent results is differences in the baseline level of delay-discounting that rats exhibit.…”
Section: Discussioncontrasting
confidence: 85%
“…These results were somewhat surprising given previous reports that suggested AMPH, at the doses tested here, decreases impulsivity (Barbelivien et al, 2008;Cardinal et al, 2000;deWit et al, 2002;Winstanley et al, 2003;van Gaalen et al, 2006). However, AMPH's effects on delay-discounting behavior are not unequivocal; it has been shown to increase (Evenden and Ryan, 1996;Cardinal et al, 2000) or have little to no effect on impulsive choice (Barbelivien et al, 2008;Uslaner and Robinson, 2006). One factor that has been suggested as a potential contributor to these inconsistent results is differences in the baseline level of delay-discounting that rats exhibit.…”
Section: Discussioncontrasting
confidence: 85%
“…This is in agreement with animal studies suggesting that STN lesions may heighten incentive motivation for food and improve RTs, however in association with increasing of premature responding (Baunez, Nieoullon, & Amalric, 1995;Uslaner & Robinson, 2006). …”
Section: Discussionsupporting
confidence: 91%
“…The 2.0 mg/kg dose increased the number of omissions and latencies to both nosepoke and lever press, with the AMPH-pretreated group exhibiting significantly more omissions than the saline-pretreated group. There are several reports indicating that acute AMPH treatment either dose-dependently reduces (Cardinal et al 2000;deWit et al 2002;Winstanley et al 2003;vanGaalen et al 2006), increases (Evenden and Ryan 1996;Cardinal et al 2000), or has little to no effect (Uslaner and Robinson 2006) on impulsive choice in a delay-discounting paradigm. It is unclear why the results of these various studies are somewhat equivocal, but differences in baseline choice behavior have been shown to influence the effects of AMPH on delay discounting.…”
Section: Discussionmentioning
confidence: 99%